Sensitivity Analysis in a Fatigue Delamination Problem of an Elastic Two-Layer Composite - FIGIEL, Ł.; LAUKE, B.; KAMIŃSKI, M. (Engineering Transactions, 2008)
Several parameters can affect the fatigue delamination growth in laminates – these include e.g. constituent material properties and/or composite shape. Knowledge about effects of these parameters can lead to a better understanding of the fatigue delamination behaviour and can also pinpoint directions for optimum composite design. These effects can be elucidated by carrying out an appropriate sensitivity analysis. A FEM-based computational approach to sensitivity analysis is proposed in this work to study composite parameter effects in a fatigue delamination problem of an elastic two-layer composite. It is used to calculate and analyse sensitivity gradients of the fracture parameter and fatigue cycle number with respect to composite design parameters such as layer elastic constants. It is observed that sensitivities computed from this approach are generally numerically stable. Obtained sensitivities pinpoint quantitatively the most and least important composite parameters that govern a fatigue delamination process. Sensitivity results are verified by another computational approach and a very good agreement is found.